A Perspective: Molecular Detections of New Agents in Finfish—Interpreting Biological Significance for Fish Health Management. Issue 2 (17th May 2022) - Meyers, Theodore R.; Hickey, Nora
Abstract: The increased sensitivity of advanced molecular techniques greatly exceeds the sensitivities of traditional detection methods for infectious agents. This sensitivity causes difficulty in interpreting the biological significance of such detections in fish (and shellfish), especially when the agent(s) cannot be cultured in the laboratory. In the Pacific Northwest, including Canada and Alaska, molecular detections of "new" (unknown or known but discovered in a different geographic location or fish host) potentially infectious agents in fish have received extensive media attention and misinterpretation that call for resource agencies to change current fish health surveillance practices or policies to include these agents. Fish health specialists from several of these agencies and organizations (see Acknowledgments) advise that any policy changes should be made only after further investigations to avoid wasting resources to conduct surveillance for organisms that are not significant to fish health or for noninfectious genetic material that does not represent a viable agent. Molecular detection is not proof of agent viability within or on host tissues and requires further investigation regarding the agent's ability to replicate and evidence that the agent causes substantial risk of disease to exposed fish populations. This document provides examples of molecularly detected agents causing public concern that were accompanied by little or no data to provide context and assessment of biological significance, highlights important questions to be answered regarding these detections, and provides a suggested pathway of investigative criteria to determine viability and pathogenicity of such agents that are necessary for consideration of any changes to aquatic animal health practices and policies.